2021
DOI: 10.33137/cpoj.v4i1.35098
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management in Persons With Limb Loss: A Systematic Review

Abstract: BACKGROUND: Self-management is an integral component of managing long-term conditions and diseases. For a person with limb loss, this self-management process involves caring for the residual limb, the prosthesis, and the prosthetic socket-residual limb interface. Failure to properly self-manage can result in unwanted secondary complications such as skin breakdown, falls, or non-use of the prosthesis. However, there is little evidence on what self-management interventions are effective at preventing secondary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Given the complex medical profile of persons with LEA, a focus on self-management support within a team-based model of care, may assist with overall physical, emotional, and social functioning of persons with LEA [ 64 ]. Self-management refers to the tasks, skills and behaviours associated with an individual’s ability to navigate the physical, social, and cognitive lifestyle factors, changes, and consequences of living with a chronic condition [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complex medical profile of persons with LEA, a focus on self-management support within a team-based model of care, may assist with overall physical, emotional, and social functioning of persons with LEA [ 64 ]. Self-management refers to the tasks, skills and behaviours associated with an individual’s ability to navigate the physical, social, and cognitive lifestyle factors, changes, and consequences of living with a chronic condition [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative research identified the need for more self-management education and training opportunities within rehabilitation to assist in the transition from hospital to community for persons with LEA [ 71 ]. To date, there is limited research on self-management and LEA [ 64 ]. In a recent systematic review, only 7 articles were identified on self-management among persons with LEA [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] This process of self-managing is crucial in the prevention of SMRC's related to limb loss, including integumentary, musculoskeletal, and functional impairments. [9][10][11] Because the importance of self-management in PwLLL is established and teaching this essential information is considered part of the standard care, [12][13][14] it is reasonable that there should be a way to objectively evaluate self-management. Self-management knowledge assessment with resultant intervention is standard care in many other health disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Because the importance of self-management in PwLLL is established and teaching this essential information is considered part of the standard care, 12-14 it is reasonable that there should be a way to objectively evaluate self-management. Self-management knowledge assessment with resultant intervention is standard care in many other health disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…With approximately two million individuals living with limb loss in the United States, it is paramount that individuals with limb loss receive appropriate treatment following this life altering event. 1 , 2 Limb loss can impact an individual's quality of life and function by limiting participation in valued activities. However, a comprehensive individualized rehabilitation program can help build a functional foundation for a safe transition back to society and daily life for individuals with limb loss.…”
Section: Introductionmentioning
confidence: 99%